2001
DOI: 10.1210/endo.142.8.8313
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Insulin, Glucose, and Pyruvate on the Kinetics of Leptin Secretion

Abstract: Leptin is a hormone that is secreted by fat cells and has roles in body weight regulation, glucose metabolism, reproduction, and other neuroendocrine functions. The purpose of this study was to determine whether the secretagogues, insulin, glucose, and pyruvate, enhance leptin secretion by increasing leptin synthesis, or whether these secretagogues stimulate the quantal release of a stored cytosolic pool of leptin. We found that in the absence of secretagogues, the rate of leptin secretion from isolated rat ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
(32 reference statements)
7
26
1
Order By: Relevance
“…The brain could monitor adipocyte function via sensory innervation of adipose tissue (34). Adipose tissue can also communicate with the brain through changes in circulating leptin levels because adipocyte leptin production responds to changes in substrate oxidation (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The brain could monitor adipocyte function via sensory innervation of adipose tissue (34). Adipose tissue can also communicate with the brain through changes in circulating leptin levels because adipocyte leptin production responds to changes in substrate oxidation (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the insulin effect on leptin depends on insulin-stimulated glucose uptake and metabolism in rat adipocytes (42,55). Mueller et al (55) concluded that insulin's effect on glucose metabolism explains its ability to stimulate leptin gene expression via a SP-1 site and thus its increased release.…”
Section: Nutrients May Signal Alterations In Leptin Productionmentioning
confidence: 99%
“…Leptin exists in different compartments from other adipocyte secretory products, namely lipoprotein lipase, adiponectin, or glucose transporter 4 (3,6,67). Inhibition of vesicular trafficking with Brefeldin A (49) or monensin (42) blocks leptin release into medium and leads to its intracellular accumulation, indicating that leptin secretion is regulated by the classical secretory pathway. However, leptin does not appear to colocalize within Golgi (3), and Roh et al (67) suggested that, at least in adipocytes from young rats, separate leptin storage vesicles may exist.…”
Section: Regulation Of Leptin Release At Posttranslational Stepsmentioning
confidence: 99%
“…For example, Thomas et al (2001) used immunocytochemistry to detect leptin protein at the maternal and fetal interface of the ovine placenta and proposed that leptin may mediate nutrient partitioning to the fetus via interaction with placental leptin receptors. Leptin synthesis is nutritionally sensitive (Levy and Stevens, 2001), with circulating concentrations varying according to the maternal body condition, dietary intake and plasma insulin concentrations (Thomas et al, 2001). Thus, the effects of body condition on leptin function and fetal growth warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%